Scleral Rupture Secondary to Idiopathic Non-Necrotizing Scleritis in a Dog. (5th June 2013) - Best, Lori J.; Newman, Shelley J.; Ward, Daniel A.; Hendrix, Diane V. H.
Abstract : Background . Canine granulomatous scleritis is an uncommon disease that can be classified as necrotizing or non-necrotizing. Clinical signs associated with scleritis are typically severe, resulting in pain and loss of vision, and response to treatment is often poor. Necrotizing scleritis has been previously associated with scleral rupture. Case Presentation . A 10-year-old male castrated Chihuahua was presented for periocular pain, tissue swelling adjacent to the limbus superiorly, chemosis, mild corneal edema and neovascularization adjacent to the superotemporal limbus in the right eye. The left eye was within clinically normal limits. Surgical exploration of the right eye revealed a scleral rupture at the inferonasal aspect of the globe. Histopathology revealed a non-necrotizing granulomatous scleritis with no infectious organisms visualized. Infectious disease testing and special histopathologic staining did not reveal an underlying infectious etiology. Conclusion . Granulomatous scleritis is a painful and vision-threatening disease that needs to be treated early and aggressively in order to avoid loss of vision or loss of the eye. Globe rupture secondary to severe non-necrotizing scleritis is an uncommon, but detrimental, clinical manifestation of this disease. This is the first case report of scleral rupture secondary to severe non-necrotizing scleritis and therefore represents a unique and interesting disease manifestation.